2020
DOI: 10.1016/j.margeo.2020.106199
|View full text |Cite
|
Sign up to set email alerts
|

Tunnel valleys of the central and northern North Sea (56°N to 62°N): Distribution and characteristics

Abstract: The analysis of buried tunnel valleys in the North Sea can provide information about the past configuration and dynamics of the Scandinavian and British ice sheets and the processes by which sediment and meltwater were transported at the ice-sheet base. However, little is presently known about the distribution and characteristics of tunnel valleys in the Norwegian sector of the North Sea. Here we use an extensive database of 3D seismic and high-resolution magnetic data to map more than 2200 tunnel valleys in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 70 publications
1
18
0
Order By: Relevance
“…They often exceed 20 km in length, which is high (cf. Ottesen et al, 2020). However, their typical width below 2 km is conformant with counterparts of the Scandinavian Ice Sheet (cf.…”
Section: Tunnel Valleyssupporting
confidence: 58%
See 1 more Smart Citation
“…They often exceed 20 km in length, which is high (cf. Ottesen et al, 2020). However, their typical width below 2 km is conformant with counterparts of the Scandinavian Ice Sheet (cf.…”
Section: Tunnel Valleyssupporting
confidence: 58%
“…Tunnel valleys are formed subglacially due to meltwater erosion either as a result of outburst floods or by a gradual or steady-state mechanism (Ó Cofaigh, 1996;Livingstone and Clark, 2016). The subglacial water flow is driven by gradients in hydraulic potential (function of the bed and ice elevation) (Shreve, 1972), resulting in orientations typically parallel to the glacier flow (Kehew et al, 2012).…”
Section: Tunnel Valleysmentioning
confidence: 99%
“…They broadly follow the protocol described by Ivanovic et al (2016), opting for a melt-uniform freshwater scenario that conserves water across the deglaciation in accordance with the prescribed ice sheets. Two sets of simulations were analysed; one uses the global ICE-6G_C ice sheet reconstruction (Peltier et al, 2015) performed at 1000year intervals from 26 to 21 ka and 500-year intervals from 21 to 0 ka (the same simulations are described in more detail by Morris et al (2018) in their Supplementary Materials and Methods), and the other uses the GLAC-1D global ice-sheet reconstruction (Briggs et al, 2014;Ivanovic et al, 2016;Tarasov et al, 2012Tarasov et al, , 2014Tarasov and Peltier, 2002) at 500-year intervals from 26 ka to present that are otherwise identical to the ICE-6G_C set. From these simulations, we extracted 50-year climate means for annual precipitation, total annual evaporation, and annual temperature for the 0.5 • × 0.5 • model grid square centred at 55 • N, 3.75 • E, which covers Dogger Bank.…”
Section: Palaeoclimate Modellingmentioning
confidence: 99%
“…Numerous studies have demonstrated the high abundance of tunnel valleys in the North Sea (Fig. 1a, Praeg, 2003; Kluiving et al ., 2003; Lonergan et al ., 2006; Kristensen et al ., 2007; Lutz et al ., 2009; van der Vegt et al ., 2012; Stewart et al ., 2013; Dove et al ., 2017; Prins and Andresen, 2019; Ottesen et al ., 2020). Few studies, however, have conducted research in the southeastern German North Sea sector between Helgoland and the Eider Valley (Lutz et al ., 2009; Winsemann et al ., 2020).…”
Section: Introductionmentioning
confidence: 99%